A Randomized Trial of Treatment for Acute Anterior Cruciate Ligament Tears - Frobell, Richard B; Roos, Ewa M; Roos, Harald P; Ranstam, Jonas; Lohmander, L. Stefan (The New England journal of medicine, 2010)
In this randomized, controlled trial of young, active adults with an acute anterior cruciate ligament (ACL) injury, rehabilitation plus early ACL reconstruction was not superior to rehabilitation plus optional delayed ACL reconstruction with respect to pain, symptoms, knee function, and knee-related quality of life, and it resulted in significantly more knee reconstructions. Rupture of the anterior cruciate ligament (ACL) is a serious knee injury that affects mainly physically active young people. The injury is characterized by joint instability that leads to decreased activity, unsatisfactory knee function, and poor knee-related quality of life in the short term, 1 , 2 and it is associated with an increased risk of osteoarthritis of the knee. 3 Surgical reconstruction of the torn ligament has been regarded as critical for a good outcome and is commonly performed, particularly in those wishing to resume sports activities. 2 , 4 , 5 Despite a lack of evidence from high-quality randomized, controlled trials comparing ACL reconstruction . . .